Internationale 69. (Geluwe : Internationale 69, 1969)
Bekaert, Piet ; Boonstra, Ger ; Boot, Eric ; Canestraro, Livia ; De Bruyne, Paul ; Dekeyser, Jef ; Deserrano, Roland ; De Maeyer, Jacky ; De Smet, Yves ; Depuydt, Stefaan ; etc.
Internationale 69, Geluwe 1969
boek